Adab sebagai faktor pengantara program pembangunan kerohanian islam dan persekitaran tempat kerja islamik - Abd Rahman, Ismail (2017)
Effective management of Human Resources Department will benefit not only to the organisation, but also individuals and society. Literature studies have shown that spirituality in the workplace can improve work behaviour, work performance and positive attitude. This study used Islamic manner (adab) as a measurement in analysing the impact of the Islamic spiritual development program. The objectives of this study are to measure the relationship between the Islamic spiritual development program and the Islamic workplace; evaluate the relationship between the Islamic Spirituality development program and adab; evaluate the relationship between adab and Islamic workplace; evaluate the mediating effect of Islamic spiritual development program and Islamic workplace; and measure moderating effect on staff categories, religious education background, and financial resources between adab and the Islamic workplace. The Structural Equation Model (SEM) was developed and tested for 284 respondents from Universiti Teknologi Malaysia, Kuala Lumpur using questionnaires. The data were analysed using Statistical Package for Social Sciences (SPSS) version 23.0 and Partial Least Square (PLS). This research findings show that there are positive relationships between Islamic spiritual development program and Islamic workplace (β=0.316, t=3.848), between Islamic spiritual development program and adab (β=0.509, t=6.181), and between adab and the Islamic workplace (β=0.565, t=5.523). For mediating effect, the result showed that adab is the intermediary factor between the Islamic spiritual development program and Islamic workplace (z= 3.599, p < 0.05). The results show that there is no moderating effect on the staff categories (t=0.656), Islamic education (t=1.309) and income (t=1.325) between adab and Islamic workplace.